Application of a new multi criteria decision making method for warehouse location problem. (2016) - Aghighi, Azam; Bisheh, Mohammad Najjartabar; Ala, Ali; Avilaq, Behzad Aslani; Dehghani, Safoora
Proper warehouse location selection is one of the most important challenges in the optimisation process of a logistics system and many quantitative and qualitative factors affect it. Therefore, through this paper a new balancing and ranking method with an interval data approach is presented. This method involves a three-step procedure to derive an overall complete final order of warehouses previously selected as possible locations. The procedure involves defining an outranking matrix based on criteria values for all available warehouse locations while taking into account the frequency of superiority of one location over others. Ordering of warehouse locations were performed based on information from an advantages-disadvantages table, distance travelled after final balancing, and the provisional order of locations. This provisional order of locations, referred to as triangularisation. In order to demonstrate effectiveness of the method it was applied to a case study and results were evaluated and verified.